The importance of socio-demographic factors on food literacy in disadvantaged communities - Araque-Padilla, Rafael A.; Montero-Simo, Maria Jose (Frontiers in Sustainable Food Systems, 2025)
IntroductionFood literacy, the ability to make informed food choices supporting health and sustainability, plays a critical role in addressing malnutrition and food insecurity, especially in disadvantaged communities. Despite its importance, much of the existing research has focused on developed countries, leaving gaps in understanding food literacy in low-income contexts. This study examines food literacy in a disadvantaged community in western Honduras, specifically analyzing how socio-demographic factors influence food-related behaviors.MethodsWe assessed food literacy levels in 400 predominantly female-headed households in a disadvantaged community in western Honduras. Using a locally adapted food literacy assessment, four dimensions were evaluated: Planning and Management, Selecting, Preparing, and Eating food.ResultsThe results revealed a moderately high overall food literacy level (average score: 82.73/114), but with significant variations across dimensions. The lowest scores were observed in Planning (66.24%) and Selecting (59.2%), indicating challenges in meal planning and choosing healthy foods. Food preparation skills were notably high, suggesting resilience despite limited resources. Socio-demographic factors such as age, income, education, and location significantly influenced food literacy. Older adults (50+) scored significantly lower than younger groups (ANOVA, p < 0.05), as did individuals with lower income levels and those residing in rural areas or small municipalities (p = 0.000 for both). Higher levels of education correlated with better food literacy, particularly in Planning (p = 0.00) and Selecting food (p < 0.05).DiscussionThe findings highlight the importance of addressing socio-economic factors such as education, income, and infrastructure to improve food literacy in disadvantaged communities. Education emerged as a key determinant of food literacy, especially in meal planning and food selection. Interventions should be designed to address these gaps, with a particular focus on older adults and rural populations. However, to achieve meaningful progress, policies that improve income levels and enhance infrastructure connecting rural and urban areas are essential. Integrating food literacy education into community programs is crucial to fostering healthier food practices.